Correlation between mean annual rainfall and its standard deviation (MAUSAM, 1965)
The hypothesis that linear relationship exists between mean rainfall and its standard deviation is tested in case of Rajasthan by obtaining correlation coefficient between them and developing linear regression. It is seen that high correlation exists and that the observed differences between the estimated and actual standard deviation are not, on the basis of Standard Error of estimate, significant. Relative error in ,the estimate is also generally small.